The Effect of Economic Growth, Minimum Wage, and Population on Labor Absorption in Regencies and Cities of Central Java Province - Tiara Amalia Puasanty; Wiwin Priana Primandhana; Wirya Wardaya (International Journal of Economics, Business and Innovation Research, 2025)
Labor absorption is one of the important indicators in the success of economic development, especially in Central Java which faces the challenge of high unemployment and lack of employment. This study aims to analyze the influence of economic growth, minimum wage, and population on labor absorption in districts/cities of Central Java Province in the 2017-2023 period. The study used a quantitative method with panel data analysis to combine time series data and cross data. The variables used include labor absorption as the dependent variable, while economic growth, minimum wage, and population number are independent variables. The results of the study show that economic growth, population number, and minimum wage have a positive influence on labor absorption.